Studying the Heavy Metals Composition and the Impact of Different Common Solvents on the Extraction Efficiency of Phytochemical Secondary Metabolites from the Leaves of Ziziphus spina-christi Grown in Jordan - Khaleel, Sabah M.J. (Pakistan Journal of Nutrition, 2018)
Objective: The purpose of this study was to investigate the impact of different common solvents on the extraction efficiency of phytochemical secondary metabolites and to determine the heavy metals composition of Ziziphus spina-christi (Z. spina-christi) medicinal plant available in Jordan. Methodology: The dry leaves from Z. spina-christi were extracted using different solvents like water, methanol, ethanol, acetone, chloroform, ethyl acetate and n-hexane. Then the extraction yield, the total of flavonoid, tannin and alkaloid contents and heavy metals concentrations of Pb, Cu, Cd, Ni and Co were investigated. Results: The highest extract yield was obtained from water extract (46.2%). Ethyl acetate has the highest flavonoids content (145.3±2.3 mg QE g–1 DW extract) while methanol extract has the highest concentration of tannins (57.2±5.8 mg GAE g–1 DW). The crude powder of Z. spina-christi leaves has appreciable amount of alkaloids (10.1±0.02 mg g–1) with permissible heavy metals concentrations. Conclusion: The yield and extraction efficiency of secondary bioactive compounds from Z. spina-christi leaves were solvent dependent. The leaves extracts of Z. spina-christi plant could be a potential source of food products and useful drugs.